Harnessing the Power of Natural Mineral Waters in Bread Formulations: Effects on Chemical, Physical, and Physicochemical Properties - Ferreira, Fernanda (2024)
This study aimed to evaluate the feasibility of incorporating natural mineral waters (NMW), including thermal water (TW) and bottled mineral water (BMW), into bread (‘biju’ type) to enhance its mineral content and explore their impacts on physicochemical, technological, biochemical, and chemical composition. NMW, rich in sodium, potassium, and magnesium, resulted in bread formulations with higher contents of these minerals and greater total mineral levels, thus potentially enriching food products. Proximate composition analysis showed no significant differences in moisture, proteins, carbohydrates, and energy, except for lipids and soluble sugars. Texture analysis revealed that water type influenced textural properties, with salt content affecting hardness, springiness, and cohesiveness. Viability analysis of Saccharomyces cerevisiae showed consistent results across formulations, suggesting water pH and mineral content did not significantly affect fermentation. In addition, bread formulations without added salt were developed to assess the potential of sodium-rich NMW as a natural source of salt. For these samples, and considering the parameters assessed, except for salt and sodium content, the differences observed were slight compared to salt-added formulations, highlighting NMW’s potential to produce low-salt bread. These findings not only enhance the value of local resources but also offer an innovative and sustainable strategy for utilizing NMW springs across Europe.